DIY as Interior Design Education “Everybody Can Be Designer” - Nurhayatu Nufut Alimin (Graduate School of Institut Seni Indonesia Yogyakarta, 2019)
DIY (Do-it-yourself) for home decor is an activity of decorating or repairing the house or making things for home independently rather than paying someone else to do it. DIY gains its popularity nowadays, particularly on the internet. The phenomena of DIY probably will make interior designer lost their job because DIY seems can give a straightforward solution for people by self-study. The present study aimed to reveal what is really going on in the field of interior design today. The researcher would like to analyze the difference between an interior designer job and DIY content sharing. The researcher collected the data from some popular DIY accounts (DIY; all things thrifty; and the house lars built), some practitioner‘s responses, and interview with the lecturer of the interior design department. The researcher attempted to answer the question usingphenomenological approach consisting of four steps namely epoche, reduction, variation of imagination, and synthesis of meaning and essence. This phenomenon arises since we begin to enter the fourth industrial revolution where internet handles everything and provides accessibility. One of the positive impacts of this phenomena is that people gain more understanding related to interior design. In other words, this phenomenon makes everybody can be a designer through DIY.